High-sensitivity cardiac troponin I and risk of cardiovascular disease in an Australianpopulation-based cohort. Issue 11 (24th October 2017) - Zhu, Kun; Knuiman, Matthew; Divitini, Mark; Murray, Kevin; Lim, Ee Mun; St John, Andrew; Walsh, John P; Hung, Joseph
Abstract : Objective: High-sensitivity cardiac troponin I (hs-cTnI) is an emerging biomarker for cardiovascular risk. We examined hs-cTnI as a predictor of mortality and cardiovascular outcomes in an Australian population-based cohort and evaluated if a sex difference exists. Methods: Serum hs-cTnI was measured in the Busselton Health Study 1994/1995 Cohort (n=3939). Outcome measures were total and cardiovascular mortality, cardiovascular disease (CVD) and coronary heart disease (CHD) events, heart failure and stroke. Results: Hs-cTnI was detectable (>1.2 ng/L) in 66.1% of participants (males 81.8%, females 54.4%) at baseline. There were 886 deaths (including 361 from CVD) and 940 CVD events during 20-year follow-up. Adjusting for Framingham Risk Score variables, hs-cTnI was a significant predictor of total mortality (HR (95% CI): 1.16 (1.09 to 1.24)), CVD mortality (1.33 (1.23 to 1.44)), CVD events (1.18 (1.11 to 1.25)), CHD events (1.11 (1.03 to 1.20)), heart failure (1.44 (1.31 to 1.58)) and stroke (1.13 (1.03 to 1.24)) per doubling of hs-cTnI at baseline. HRs remained significant in CVD-free individuals at baseline (n=3215), except for CHD events. There were no significant interactions between sex and hs-cTnI as a predictor of outcomes. Compared with individuals with hs-cTnI ≤1.2 ng/L, men with hs-cTnI ≥6.0 ng/L and women with hs-cTnI ≥4.0 ng/L had an HR of 2.18 (1.42 to 3.37) and 1.84 (1.30 to 2.62), respectively, for any CVD event, which persisted in the CVD-free subgroup. Conclusions: Cardiac troponin I, measured with a high-sensitive assay, is an independent predictor of fatal and non-fatal CVD events and may help identify at-risk individuals in a general population.